Impact of Human Resource Management Systems, Organizational Citizenship Behavior on Organizational Performance: Quantitative Study in University Settings - Sarwar, Huma (Archives of Business Research, 2017)
This study is aimed at investigating the impact of Human Resource Inputs (Motivation) & Human Resource Practices (T&D) on Human Resource Outputs (Employee Performance) of the faculty members working in different colleges and universities in Pakistan. 150 structured survey questionnaires were sent through for data collection from the faculty members of Universities/Institutes of Pakistan and after multiple responses 120 questionnaires were received. The results of the study showed that human resource management systems have statistically significant relationship with employee performance and organizational citizenship behavior. The study helps the management of the Universities/Institutes of Pakistan in improving employee performance both in colleges and universities based in Pakistan.